L04 Risperidone long acting injection stabilises juvenile Huntington's disease: case series. (16th November 2010) - Johnston, L; Johnston, T
Abstract : Objective: There is currently no known disease altering treatment for juvenile Huntington's disease. Successful symptomatic treatment often involves antipsychotic medication. Non-adherence to such medication is a practical problem yet the effect of depot antipsychotic medication remains largely unknown. Case series: A period of non-drug adherence to oral risperidone in four patients with juvenile Huntington's disease, after appearing to show symptomatic improvement, suggested a possible role for risperidone long acting injection (LAI). The patients gave prior informed consent to receiving a fortnightly injection at a dose of 25 mg. Observations were based on patients, carers and staff reports. At the end of 4–12 months (mean 9 months), the four patients showed symptomatic stabilisation with earlier initiation appearing more effective. Conclusions: This case series suggests risperidone LAI may be a viable symptomatic treatment strategy in similar patients. Drug non-adherence may be more common than previously thought. Larger studies, with early initiation of antipsychotic treatment in the disease course, are required to confirm these findings. If replicated, these findings have the potential to change the symptomatic management of patients with juvenile Huntington's disease.